Effect of restricted watering and its combination with root pruning on root growth capacity, water status and food reserves of Pinus caribaea var. hondurensis seedlings - Abod, Sheikh Ali; Sandi, Simon (Martinus Nijhoff/Dr. W. Junk Publishers, 1983)
Six-month old Pinus caribaea var. hondurensis seedling were subjected to various regimes of restricted watering and their combinations with root pruning to determine a suitable technique of producing seedlings with optimum physiological condition for successful bare-root planting. From the range of treatments tested, plants subjected to watering once every 9 days (D9) were found to be the 'hardest' in terms of highest root growth capacity, leaf water content, root starch content and in having a moderately low transpiration rate. P. caribaea seedlings subjected to this preconditioning treatment may be more able to survive bare-root planting. © 1983 Martinus Nijhoff/Dr W. Junk Publishers.